MENTAL HEALTH AMONG UNIVERSITY STUDENTS: CHALLENGES AND SOLUTIONS (Ustozlar uchun, 2026)
One of the most significant problems facing college students globally is mental health. Students' psychological well-being can be greatly impacted by a variety of factors, including family expectations, financial hardships, academic pressure, and career uncertainty. In addition to lowering academic achievement, poor mental health also has an impact on social interactions, physical health, and general quality of life. This article explores the main causes of mental health issues among college students, looks at their effects, and offers doable solutions that both students and educational institutions can implement to enhance psychological wellbeing. The essay suggests that promoting healthy lifestyles and fostering a supportive learning environment are crucial for students' academic and personal success.